Achievements And Current Challenges In Modern Dermatology (Eurasian Medical Research Periodical, 2025)
Modern dermatology has made significant advancements in diagnosing and treating various skin conditions through innovative technologies such as artificial intelligence, laser therapy, and biologic treatments. These developments have improved patient outcomes, early disease detection, and personalized treatment approaches. However, challenges remain, including the increasing prevalence of skin disorders, access to advanced therapies, and ethical concerns related to AI-driven diagnostics. This article explores the latest achievements in dermatology while addressing the pressing issues that need further research and innovation